Juridical Analysis of Non-Fulfillment of the Access Principle to the Legal Counsel in Theft Criminal Cases - Arifin, Imam Malik; Arifai, Arifai; Rahim, Abdul Jabal (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of the study is to know juridical analysis of non-fulfillment of the access principle to the legal counsel in theft criminal cases. The type of this research is Normative Legal Research using a Legislative and a Conceptual Approaches. The Public Prosecutor's indictment cannot be accepted as it was made based on an invalid (legally flawed) Investigation Report (BAP) and was not in accordance with the right of due process of law. Legal aid and the defendant must be accompanied by a legal advisor as regulated in Article 56 of the Criminal Procedure Code so that this creates a gap for the legal advisor in filing an exception and the exception becomes the judge's consideration in making a decision that the public prosecutor's indictment is null and void (Null and Void), as for example in the Interim Decision of the Tapak Tuan District Court Number 106/ Pid.B /2019/ PN.Ttn, which is threatened with imprisonment for a maximum of 7 (seven) years in accordance with the provisions of Article 363 Paragraph (1) 4 of the Criminal Code in conjunction with Article 64 paragraph (1) Criminal Code. However, during the investigation process, he was not accompanied by a legal advisor, making the Investigation Report (BAP) being invalid as well as null and void